ENGLISH-INDONESIAN CODE SWITCHING SPOKEN BY ENGLISH TEACHER OF MODERN ISLAMIC BOARDING SCHOOL - Jamaluddin, Jamaluddin; Hasanah, Uswatun (State Islamic University of Sulthan Thaha Saifuddin Jambi, 2014)
Abstract Recently, many people able to use more than one language in communication with people around them. Code switching is one of the embodiment of this fact. An English teacher is expected to be able use English when he teach in classroom, but some An English teacher recognized that they sometimes use Indonesian in classroom with some benefits of it. The purpose of this study is to find out types and function of code switching, to identify factors influencing code switching, and to know how the using of code switching spoken by English teacher of Modern Islamic Boarding School Al-Hidayah Jambi. The researcher used descriptive qualitative approach as method for analyzing the data. The researcher collected the data by recording, interview and observation. The types of code switching were observed by researcher only focus on the grammatical aspects. As the result, researcher found that teacher used three types of code switching in classroom. Next, functions of code switching that found by researcher were ten functions Then, teacher recognized that there were some factors influencing code switching. Key words : Code switching, English teacher, Islamis Boarding School